Expression of Simian Retrovirus Type D Serotype 2 Envelope in Insect Cell Using Baculovirus Expression Vector System - DIAH ISKANDRIATI; MOHAMAD SADIKIN; JOKO PAMUNGKAS (Indonesian Society for microbiology, 2009)
Simian retrovirus type-D (SRV) is a causative agent of simian acquired immunodeficiency syndrome in Asian macaques, and can serve as a viral model in understanding of retrovirus infection because of some similarities to human AIDS pathogenesis. Study of infection and pathogenesis of SRV in macaques could be a strategy of vaccine and antiviral development for preventive and therapeutic purposes. We expressed the SRV-2 envelope gene using baculovirus expression vector system and transfected it to Spodoptera frugiferda insect cell line for SRV-2 recombinant protein production. Analysis using PCR and sequencing technique of recombinant in the passage-3 viral stock indicated the occurrence of recombination between SRV-2 envelope and baculovirus genome. Purification using immobilized metal ion affinity chromatography Ni2+-NTA to recombinant protein could minimize the presence non-specific proteins. The SDS-PAGE analysis showed a specific protein for SRV-2 gp70 envelope. Western blot analysis of this purified protein indicated a specific reaction with anti-SRV-2 antibody positive of Macaca fascicularis serum shown as SRV-2 gp70 envelope band.